Optimizing Business Corn Silk as A Fungctional Drink to Enhance Body Immunity - Reni Aprilliya Linawati; Rohmawati Kusumaningtias (IAEI, 2023)
Corn silk is an organic waste that has no selling value so if it is not used properly it will pollute the environment by causing bacteria and bad odors. Corn silk contains the minerals calcium, potassium, magnesium, sodium, essential oils, alkaloids, saponins, tannins and flavonoids, proteins, carbohydrates, fiber, vitamins B, vitamin C, vitamin K, steroids (sitosterol and stigmasterol), and protocatechin acid ( compounds polyphenols) which are good for consumption for people with cholesterol, diabetes and hypertension. The purpose of this study was to analyze the benefits of corn silk which is processed into a functional drink in the form of milk. The method applied is a literature review by reviewing some of the previous literature and calculating BEP (Break Event Point), ROI (Return On Investment) and NPV (Net Present Value). This research gives the result that this product has a positive value with a total ROI of 33% and has an NPV between present value and cash flow in the next year of IDR 20,998,440. Based on the financial projection analysis that has been carried out, it shows that the corn hair milk business is feasible to implement.